2015
DOI: 10.3402/jev.v4.27522
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes serve as tumour markers for personalized diagnostics owing to their important role in cancer metastasis

Abstract: Exosomes, membrane vesicles of 40–100 nm in diameter, are derived from endosomes in various cells. The bioactive molecules specifically packed into exosomes can be horizontally transferred into recipient cells changing their biological properties, by which tumour cells continuously modify their surrounding microenvironment and distant target cells favouring cancer metastasis. It has been suspected for a long time that exosomes participate in the whole process of tumour metastasis. Although there is much unknow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
213
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(218 citation statements)
references
References 146 publications
(118 reference statements)
4
213
0
1
Order By: Relevance
“…As discrete packages of protein and RNA emanating directly from tumor cells, exosomes have a number of advantages when considered as biomarkers: exosomes protect their protein cargo from proteolytic digest; they can be purified from plasma or sera, reducing the dynamic range of this matrix; and previous studies have demonstrated that the number of exosomes in circulation increases in cancer patients (52). Accordingly, exosomes purified from blood and urine are now being assessed as markers for a wide range of malignancies, including prostate (53), lung (54), breast (55), and ovarian cancers (56), among others (33). The work performed in this study now enables a targeted examination of potential protein markers of CCA in exosomes not only from blood but other matrices such as urine and saliva.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discrete packages of protein and RNA emanating directly from tumor cells, exosomes have a number of advantages when considered as biomarkers: exosomes protect their protein cargo from proteolytic digest; they can be purified from plasma or sera, reducing the dynamic range of this matrix; and previous studies have demonstrated that the number of exosomes in circulation increases in cancer patients (52). Accordingly, exosomes purified from blood and urine are now being assessed as markers for a wide range of malignancies, including prostate (53), lung (54), breast (55), and ovarian cancers (56), among others (33). The work performed in this study now enables a targeted examination of potential protein markers of CCA in exosomes not only from blood but other matrices such as urine and saliva.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, great interest has been shown in exploiting circulating exosomes as biomarkers of disease or as a mechanism for reducing the dynamic range of the circulating proteome (33). In order to identify potential circulating markers of CCA, we characterized the proteome of exosomes secreted by the KKU055 human CCA cancer cell line and compared them to CCA-associated proteins identified in the hamster experiments.…”
Section: Validation Of Itraq Data Using Immunoblotting and Immunohistmentioning
confidence: 99%
“…15 Exosomes are a subset of extracellular vesicles (EVs), which are lipid bilayer vesicles secreted from cells. 16 Exosomes have a diameter of 30-200 nm, and they transfer miRNA, mRNA, DNA, and proteins to other cells, thereby mediating intercellular communications.…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes can be taken up by other cells, it is possible that these membrane vesicles could serve as a novel way of intercellular communication and signaling (5). Over the past few years, researchers have revealed that exosomes crosstalk and/or influence major signal pathways in tumor progression, such as hypoxia-driven epithelial-to-mesenchymal transition, angiogenesis and metastasis involving many cell types within the tumor microenvironment (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%